(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Supraglottic airway devices are widely used during short elective procedures because they are easier to insert and less invasive than endotracheal tubes. Among them, the classic laryngeal mask airway (LMA) and the second-generation I-gel are both well-established devices. The present study compared their performance in adults undergoing minor surgical procedures under total intravenous anaesthesia (TIVA). Methods: This hospital-based comparative study was conducted in the Department of Anaesthesiology, Gandhi Medical College and Hospital, Secunderabad, from June 2023 to November 2024. Ninety adult patients aged 18 to 60 years, belonging to ASA I or II, and scheduled for minor elective procedures under TIVA were enrolled and randomly allocated into two equal groups: I-gel (n=45) and LMA (n=45). Outcomes included insertion time, number of attempts, oxygen saturation, haemodynamic variables, airway manipulation, trauma, and postoperative sore throat. Continuous variables were compared using the independent t-test, while categorical variables were analysed using the chi-square test or Fisher’s exact test where appropriate. A p value <0.05 was considered significant. Results: Baseline characteristics were comparable between the two groups. Mean insertion time was significantly shorter with I-gel than with LMA (12.32 ± 2.05 s vs 16.01 ± 2.10 s; p<0.001). All patients in both groups had successful insertion on the first attempt. Mean oxygen saturation remained comparable in the I-gel and LMA groups (98.43 ± 1.01% vs 98.57 ± 0.78%; p=0.465). Heart rate and diastolic blood pressure were similar at all measured time points. Systolic blood pressure differed significantly only at 5 minutes, being higher in the I-gel group (122.67 ± 14.76 mmHg vs 116.09 ± 14.63 mmHg; p=0.037). Airway manipulation was required in 26.67% of cases in each group. Trauma was noted in 11.11% of the I-gel group and 4.44% of the LMA group (p=0.238), while postoperative sore throat occurred in 6.67% and 11.11% respectively (p=0.459). Conclusion: Both I-gel and LMA were safe and effective for airway management during minor procedures under TIVA. I-gel offered a clear advantage in terms of faster insertion, while other perioperative outcomes were largely comparable. These findings support the use of I-gel as a practical alternative to LMA in suitable elective cases.